Type 1 diabetes complicated with cyclic vomiting syndrome and exogenous insulin antibody syndrome: A case report - Geng, Leiluo; Diao, Xue; Han, Hao; Lin, Ying; Liang, Wei; Xu, Aimin (Frontiers in Endocrinology, 2022)
Every fifth individual with type 1 diabetes (T1D) suffers from an additional autoimmune disorder due to shared genetic factors and dysregulated immunity. Here we report an extremely rare case of T1D complicated with cyclic vomiting and hypoglycaemia. A 27-year-old Chinese woman with 14-year history of T1D was periodically hospitalized for severe vomiting of more than 30 times a day without apparent organic causes. The vomiting developed acutely and remitted spontaneously after 2-3 days, followed with intractable hypoglycaemia for another 3-4 days during the hospitalization. A few weeks after discharge, she was admitted once again with the same symptoms and disease course. Cyclic vomiting syndrome (CVS) was diagnosed according to the Rome IV criteria, a system developed to define the functional gastrointestinal disorders. Dynamic association and disassociation of exogenous insulin and insulin antibodies (IAs) were identified in her blood during hypoglycaemia, leading to the diagnosis of exogenous insulin antibody syndrome (EIAS). Treatment with rituximab to suppress the IAs was associated with a striking amelioration of hypoglycaemia. Unexpectedly, the episodes of cyclic vomiting were also dramatically reduced. In conclusion, we identified the first case with alternating CVS and EIAS in the setting of T1D. Dynamic measurements of free and total insulin are helpful for the diagnosis of EIAS. CVS is likely to be a latent autoimmune disorder considering the good response to rituximab treatment.